(untitled) (Global Journal of Medical Research, 2013)
Laparascopic cholecystectomy is considered the treatment of choice for cholelithiasis. Laparosopic cholecystectomy can be safely performed in patients with acute cholecystitis, but there is a difference between conversion rates in patients operated within 72 hours from the onset of the symptoms and those after. The main reason for conversion on early laparoscopic cholecystectomy is the inflammation that interferes and makes the anatomy of the Calot’s triangle less visible, while other factors for the conversion of laparoscopic cholecystectomy in acute cholecystitis are the timing of the operation, age, BMI, CRP, white blood cell count (WBC), fever, tenderness in the right upper abdomen and ultrasonographic finding of extremely thickened gallbladder wall, close relation of the Hartmann’s pouch with hepaticoduodenal ligament, the gallbladder size and the number and size of stones. Case presentation: Here we present a case of 74 year old female patient, who presented at our institution with 6 day history of abdominal pain, nausea and fever, with physical, laboratory and ultrasound signs of acute cholecystitis.